Cast Syndrome: Breaking Self-Perpetuating Circle through Increased Medical Awareness - Kalisz, Agnieszka; Kozakiewicz, Julia; Okońska, Aleksandra; Kościelecki, Kamil; Skorulska, Iwona; Mączewska, Klaudia; Długozima, Patrycja; Grzeszczuk, Paulina; Grywińska, Weronika; Głowacka, Aleksandra (Quality in Sport, 2025)
Introduction: This review study intends to highlight that symptoms as common as nausea, vomiting, early satiety, and postprandial pain, could be caused by a potentially life-threatening easy to diagnose gastrointestinal disorder that could be overlooked if not known. Materials and methods: A review of chosen literature in the PubMed, Google Scholar, Web of Science database was conducted, using the following keywords: "Cast syndrome", "Superior Mesenteric Artery Syndrome", "SMA Syndrome", "Wilkie’s syndrome" Summary: Cast syndrome or Superior Mesenteric Artery (SMA) Syndrome is a condition caused by the compression of the third portion of the duodenum between the superior mesenteric artery and the abdominal aorta. The syndrome is often associated with significant weight loss, anatomical predisposition, and certain medical conditions that reduce mesenteric fat. Conclusions: Superior Mesenteric Aortic syndrome contributes to a vicious cycle that significantly affects patients suffering from it. Increasing medical awareness is essential to reduce the likelihood of diagnostic errors. Patients who are malnourished and frequently experience nausea and upper abdominal pain should undergo thorough diagnostic evaluation to prevent misdiagnosis and incorrect assumptions. Effective management of SMAS relies on physician engagement and proper education, with treatment often leading to a simple surgical intervention that boasts a high success rate.